Food price and availability in Solomon Islands during COVID-19: A food environment survey - Farrell, Penny; Bogard, Jessica; Thow, Anne; Boylan, Sinead; Johnson, Ellen; Wate, Jillian Tutuo (SAGE Publications, 2023)
Background: In Solomon Islands, the retail food environment is an important food source, for instance, the dominant source of fresh fruit and vegetables for urban consumers is open markets. The effects of COVID-19 mitigation measures (such as restriction of human movement and border closures) in early 2020 placed food security at risk in many parts of the community. Of particular concern was the risk of price gouging in an already price-sensitive market. Aims: The study aimed to provide rapid and policy-relevant information on the pricing of foods in the urban food environment in Solomon Islands in the context of the unfolding COVID-19 pandemic. Methods: A vendor survey was conducted in July to August 2020 and repeated in July 2021 using a survey tool that collected information on type, quantity, and price of food on offer. Findings: We found price reductions among the majority of fresh fruit and non-starchy vegetables available. A trend of rising prices was reported for some other commodities, such as fresh locally caught fish. Conclusion: Our findings highlight the impact of 'schocks to the system' on food prices as a potential barrier or enabler to consumption of fresh foods purchased from urban areas – an important finding in a price sensitive market. The survey design was successful in collecting pricing data from the retail food environment during a time of external ‘shock to the system’. Our approach is applicable to other settings needing a rapid survey of the external food environment.